Respostas

A melhor resposta!
  • Usuário do Brainly
2013-10-30T18:41:35-02:00
Vejamos:

6)
2 - logx (2) - log2 (x) = 0 
2 - logx (2) - 1/[logx (2)] = 0 
2 - k - 1/k = 0 
2.k - k.k - 1/k . k = 0 <=> 
2k - k² - 1 = 0 <=> 
k² - 2k + 1 = 0 <=> 
(k - 1)² = 0 <=> k = 1 
logx (2) = 1 <=> x^1 = 2 <=> x = 2 
x = p = 2
Resposta: B 

7)
log (8 + x - x²) = 1 + log (2x-5)?
Log (8 + x - x²) = Log2 + log (2x-5)
Log (8 + x - x²) = log 2*(2x-5)
Log (8 + x - x²) = log (4x - 10)
8 + x - x² = 4x - 10
- x² - 3x + 18 = 0

x'= -3
x" = +6

Espero ter ajudado! Não se esqueça de votar na melhor resposta!
Abraços!
1 5 1